Comparing the efficacy of nano crystalline silver dressing versus betadine dressing in management of diabetic foot ulcer - Singh, Bhavkeerat; Kapoor, Sudershan; Gupta, Arun Kumar (International Surgery Journal, 2020)
Background: The incidence of diabetes and its complications is rising as a result of the lifestyle changes. The foot is most frequent site for complication in patients with diabetes. Dressings have a vital part to play in the management of wounds. The ideal antiseptic is one that is lethal to all forms of bacteria, has no deleterious effect on healing tissues, delineates the operative areas, easily applied and has wide spectrum of activity and absence of acquired bacterial resistance. Nanotechnology makes it possible to expand the surface area of silver particles markedly to nanoscale. They expand the surface area of silver particles increasing their contact with bacteria. Methods: In the proposed study, over a period of 18 months, 60 cases (30-30 in 2 groups) of diabetic foot ulcers were studied with respect to response (healing) to nano silver dressing and betadine dressing after dividing them randomly. Assessment was based on various parameters like size reduction, healthy granulation tissue, etc. Results: It was seen that percentage reduction in size, was more in nano silver group as compared to betadine group. Wounds were managed successfully, early in nano silver group and wound healing was better in nano silver group as compared to betadine group. Also, nano silver was better antimicrobial. Conclusions: The prospective study showed nano silver gel is safe and effective in wound management and gives better efficacy and faster response as compared to traditional betadine dressing.